Needs of an uninsured equity-deserving minority patient cohort with physical disabilities during the first wave of the COVID-19 pandemic - Claus, D; Draganich, C; Berliner, J; Niehaus, W; Berliner, J; Magnusson, D; Smith, A. C. (Frontiers in Rehabilitation Sciences, 2023)
Title: Needs of an uninsured equity-deserving minority patient cohort with physical disabilities during the first wave of the COVID-19 pandemic. Authors: Claus D, Draganich C, Berliner J, Niehaus W, Berliner J, Magnusson D, Smith AC. Institutions: University of Colorado School of Medicine, Craig Hospital, Regis University. Background: Patients with disabilities and those from diverse equity-deserving backgrounds have been disproportionately affected by the SARS COV-2 (“COVID-19”) pandemic. Objective: To describe the significant needs and social determinants of health that affected a group of uninsured patients (from equity-deserving groups) with rehabilitation diagnoses during the early months of the COVID-19 pandemic. Design: Retrospective cohort study utilizing a telephone-based needs assessment from April to October, 2020. Setting: Free interdisciplinary rehabilitation clinic serving patients with physical disabilities from equity-deserving minority backgrounds. Participants: 51 uninsured, diverse patients with spinal cord injuries, brain injuries, amputations, strokes, and other diagnoses requiring interdisciplinary rehabilitation care. Methods: Using a non-structured approach, telephone-based needs assessments were collected monthly. Reported needs were summarized into themes and the frequencies of each theme were recorded. Results: From the total number of concerns, medical issues were reported with the highest frequency (46%), followed by equipment needs (30%) and mental health concerns (30%). Other frequently mentioned needs centered around themes of rent, employment, and supplies. Rent and employment were more frequently cited in earlier months, and equipment problems were more frequently cited in later months. A minority of patients reported they had no needs, some of whom had acquired insurance. Conclusions: Our objective was to describe the needs of a racially and ethnically diverse set of uninsured individuals with physical disabilities seen at a specialized interdisciplinary rehabilitation pro bono clinic during the early months of COVID-19. Medical issues, equipment needs, and mental health concerns were the top three needs. To optimally serve them, care providers must be aware of current and future needs for their underserved patients, especially if future lockdowns occur.